KARAKTERISTIK PENDERITA KUSTA DI PUSKESMAS ABEPANTAI KOTA JAYAPURA TAHUN 2020 - Ludia Maria Anastasia Porong; Indra Taufik Sahli; Asrianto Asrianto (POLTEKKES KEMENKES JAYAPURA, 2020)
Leprosy is a chronic infectious disease caused by Mycobacterium leprae that attacks the skin, peripheral nerves, mucosa of respiratory tract and eyes. The aim was to determine the characteristics of leprosy disease of Health Center Abepantai in 2020, based on the type of leprosy, staining of Ziehl Neelsen (ZN), age, sex and occupation. This method is a descriptive study with cross sectional design. The results, MB type highest percentage which is 8 (67%), the positive ZN staining which is 4 (33%) and negative which is 8 (67%), the age the highest percentage 16-30 level years which is 5 (42%), sex the highest percentage male sex which is 8 (67%), occupation the highest farmer which is 5 (42% ). The conclusion characteristics of leprosy Health Center in Abepantai 2020: leprosy the highest percentage which is MB type, age the highest percentage which is 16-30 years old, the highest percentage which is male sex and the highest percentage occupation which is farmer.